2010
DOI: 10.1063/1.3441373
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of peak quantum efficiency and efficiency droop in III-nitride visible light-emitting diodes with an InAlN electron-blocking layer

Abstract: InAlN electron-blocking layers (EBLs) are shown to improve the emission intensity and to mitigate the efficiency droop problem in III-nitride-based visible light-emitting diodes (LEDs). Using an In0.18Al0.82N EBL in blue LEDs, we have achieved a significant improvement in the electroluminescence emission intensity and a mitigated efficiency droop compared to similar LEDs without an EBL or with an Al0.2Ga0.8N EBL. This indicates that an In0.18Al0.82N EBL is more effective in electron confinement and reduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
98
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(98 citation statements)
references
References 17 publications
0
98
0
Order By: Relevance
“…Hence, tremendous efforts have been devoted to overcoming this drawback and thus to improving the LED performance. Thus far, novel structures including InAlN electron-blocking layer [3] and InGaN staircase electron injector [4], graded thickness quantum barriers [5], p-doped quantum barriers [6], and gradual InGaN QWs [7] etc, have been reported to reduce the efficiency droop.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, tremendous efforts have been devoted to overcoming this drawback and thus to improving the LED performance. Thus far, novel structures including InAlN electron-blocking layer [3] and InGaN staircase electron injector [4], graded thickness quantum barriers [5], p-doped quantum barriers [6], and gradual InGaN QWs [7] etc, have been reported to reduce the efficiency droop.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al employed thin AlInN barriers to suppress the thermionic carrier escape rate [10]. Additionally, electron blocking layers (EBL) that improve the emission of InGaN/GaN LEDs, including stepwise-stage EBL [11], p-type AlGaN/GaN superlattice with a graded AlN composition [12], AlGaN EBL with graded AlN fraction [13], and even AlInN EBL [14] has also been studied. Recently, it has been shown that three-dimensional hole gas [15] is effective in increasing the hole concentration, thus enhancing the optical power.…”
mentioning
confidence: 99%
“…Therefore, the polarization-matched quarternary AlGaInN and InGaN quantum barriers have been suggested to reduce the polarization field in the active region and have been experimentally demonstrated to enhance the light-output power and to reduce the efficiency droop of LEDs [23,24]. It has been also reported that p-AlGaInN and p-AlInN EBL in LED structures can prevent carrier leakage over the EBL [25,26].…”
Section: Introductionmentioning
confidence: 99%